2009
DOI: 10.3171/2009.4.peds08411
|View full text |Cite
|
Sign up to set email alerts
|

Survival and functional outcome of childhood spinal cord low-grade gliomas

Abstract: Object Intramedullary spinal cord low-grade gliomas (LGGs) are rare CNS neoplasms in pediatric patients, and there is little information on therapy for and outcome of these tumors in this population. Furthermore, most patient series combine adult and pediatric patients or high- and low-grade tumors, resulting in controversial data regarding optimal treatment of these children. To clarify these issues, the authors performed a regional population-based study of spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
4
28
1
Order By: Relevance
“…Age distribution of our cases is similar to that reported by O'Sullivan et al 10 Scheinemann et al 11 reported the same age with 5.8 years in their study on spinal glioma patients, but most of their patients (41%) were under 4 years. The male/ female ratio in their study was 2.6.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Age distribution of our cases is similar to that reported by O'Sullivan et al 10 Scheinemann et al 11 reported the same age with 5.8 years in their study on spinal glioma patients, but most of their patients (41%) were under 4 years. The male/ female ratio in their study was 2.6.…”
Section: Discussionsupporting
confidence: 85%
“…Intraspinal tumors in children are low-grade and progress slowly, and therefore their diagnosis can be delayed. The interval between symptom onset and diagnosis was approximately 10 months in the case of low-grade tumors 11,13 and 2e7 months in the case of high-grade tumors. 14e16 The high rate of severe deficit was probably due to delays in admission to our center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43] The overall GTR rate in our series (38%) was lower than that previously reported by some authors 4 but in line with the rate reported by others. 44 In contrast to earlier studies, 2,33 our results support the beneficial role for GTR, where feasible, in long-term disease survival and prevention of disease progression over extended follow-up. 30 The predictive value of extent of resection was maintained across our cumulative case series.…”
Section: Extent Of Resectioncontrasting
confidence: 56%
“…2,9,22,26,32,33,36,44,46 The overall rate of tumor progression in our series was 47%, with a mean onset of 3 years postoperatively (mean [± SEM] 3.3 ± 1 years, range 0.1-20 years). Radiotherapy was used following disease progression or recurrence in 51% of the 55 patients, while chemotherapy was used in 29% of the patients.…”
Section: Role Of Adjunct Therapymentioning
confidence: 98%